2011
DOI: 10.1177/003335491112600408
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis A Virus Antibodies in the U.S.: Results from the National Health and Nutrition Examination Survey

Abstract: Increases in seroprevalence among children in vaccinating states suggest a positive effect of the 1999 vaccination recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 10 publications
(21 reference statements)
5
30
0
1
Order By: Relevance
“…The increase in the prevalence of anti-HAV among U.S.-born children between 1999-2000 and 2009-2010 is indicative of increased protection against HAV infection through greater vaccination coverage, as has been suggested previously (58). However, during 2009-2010, an estimated 50% or more of non-Hispanic white and non-Hispanic black children aged <19 years still lacked anti-HAV protection.…”
Section: Discussionmentioning
confidence: 59%
“…The increase in the prevalence of anti-HAV among U.S.-born children between 1999-2000 and 2009-2010 is indicative of increased protection against HAV infection through greater vaccination coverage, as has been suggested previously (58). However, during 2009-2010, an estimated 50% or more of non-Hispanic white and non-Hispanic black children aged <19 years still lacked anti-HAV protection.…”
Section: Discussionmentioning
confidence: 59%
“…Many studies have found a poverty level to be related to serum hepatitis A antibody positivity (Bell et al, 2005) (Verma and Khanna, 2012). Other studies have not found statistically significant association between hepatitis A serum antibody positivity and poverty level (Klevens et al, 2011). The association between hepatitis A serum positivity and poverty has been found to be U-shaped.…”
Section: Discussionmentioning
confidence: 98%
“…Age, ethnicity, poverty and country of birth were found to be important risk factors for serum hepatitis A serum positivity (Bell et al, 2005). 1n 1995, hepatitis A vaccines were licensed in U.S., shortly after Advisory Committee on Immunization Practices (ACID) recommended vaccinations for children older than 2 years old (Klevens et al, 2011) for the high risk groups. By 1999, the vaccines were introduced to 11 Western states in U.S. with high hepatitis A virus infection rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In USA during 1999-2006, the overall seroprevalence of anti-HAV was 34.9% [7]. During 1999-2006, U.S.-born children living in vaccinating states had a higher seroprevalence.…”
Section: Discussionmentioning
confidence: 99%